The Jews in late ancient Rome : evidence of cultural interaction in the Roman diaspora - Rutgers, Leonard Victor. (Religions in the Graeco-Roman World, 1995)
The Jews in Late Ancient Rome focusses on the Jewish community in third and fourth century Rome, and in particular on how this community related to the larger non-Jewish world that surrounded it. The book's point of departure is a refutation of the disputable thesis that Roman Jews lived in complete isolation. The book examines Jewish archaeological remains and Jewish funerary inscriptions from Rome from various angles, and compares them with Pagan and early Christian material and epigraphical remains. In the last part the author concentrates on an enigmatic legal treatise entitled the Collatio , identifying its author and exploring the implications of this identification. This study proposes a new way in which the relationship between Jews and non-Jews in late antiquity can be studied.